TO STUDY THE EFFECT OF YOGIC EXERCISE ON MUSCULAR STRENGTH AND ENDURANCE OF STATE-LEVEL HANDBALL PLAYERS AGED 14-18 YEARS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study looked into how doing yoga exercises can help handball players get stronger and have better stamina. Forty players (N=40) from Mumbai, ages 14 to 18 were selected as a sample. The Experimental Group (N=20) was one of two randomly selected groups. Then, there was the Control Group (N=20).The players in the Experimental Group did yoga exercises three times a week. Each session is 90 minutes, for six whole weeks. The Control Group didn’t do any special training at all. They just kept up with their usual activities.To see the effect of yogic training on their fitness a Handgrip Dynamometer was used for strength tests, while sit-ups helped us check their endurance. Analysis was done based on data collection before and after the training using the dependent 't' test.The Experimental Group showed significant improvements in both muscular strength & endurance due to those yogic exercises. So, this method of training worked to boost the physical skills of handball players at the state level.